Multimaterial topology optimization of variational inequalities - Myśliński, Andrzej (Instytut Badań Systemowych. Polska Akademia Nauk, 2015)
The paper is concerned with the analysis and numerical solution of multimaterial structural optimization problems for bodies in unilateral contact. Contact phenomenon is governed by the elliptic variational inequality. The structural optimization problem consists in finding such topology of the domain occupied by the body that the normal contact stress along the boundary of the body is minimized. The cost functional is regularized by the multiphase volume constrained Ginzburg-Landau energy functional. The first order necessary optimality condition is formulated. The optimal topology is obtained as the steady state of the phase transition governed by the generalized Allen-Cahn equation. The optimization problem is solved numerically using operator splitting approach combined with the projection gradient method. Numerical examples are provided and discussed.
10 pages ; 21 cm
Bibliography p. 9-10
Keywords: Topology optimization; Optymalizacja topologii; Unilateral contact problems; Jednostronne problemy z kontaktem; Multimaterials; Multimateriały; Phase field regularization; Regularyzacja pola fazowego